How has the COVID-19 pandemic affected gastrointestinal surgery for malignancies and surgical infections? - Ishibashi, Yusuke; Tsujimoto, Hironori; Sugasawa, Hidekazu; Mochizuki, Satsuki; Okamoto, Koichi; Kajiwara, Yoshiki; Shinto, Eiji; Takahata, Risa; Kobayashi, Minako; Fujikura, Yuji; Hase, Kazuo; Kishi, Yoji; et al. (Nagoya journal of medical science, 2021)
The coronavirus disease 2019 (COVID-19) pandemic has affected infection control and prevention measures. We investigated the impact of the COVID-19 pandemic on postoperative infections and infection control measures in patients underwent gastrointestinal surgery for malignancies. We retrospectively evaluated changes in clinicopathological features, frequency of alcohol-based hand sanitizer use, frequency of postoperative complications, and microbial findings among our patients in February-May in 2019 (Control group) and 2020 (Pandemic group), respectively. Surgical resection in pathological stage III or IV patients was more frequently performed in the Pandemic group than in the Control group (P = 0.02). The total length of hospitalization and preoperative hospitalization was significantly shorter in the Pandemic group (P = 0.01 and P = 0.008, respectively). During the pandemic, hand sanitizer was used by a patients for an average of 14.9±3.0 times/day during the pandemic as opposed to 9.6±3.0 times/day in 2019 (p<0.0001). Superficial surgical site infection and infectious colitis occurred less frequently during the pandemic (P = 0.04 and P = 0.0002, respectively). In Pandemic group, Enterobacter, Haemophilus, and Candida were significantly decreased in microbiological cultures (P < 0.05, P < 0.05, P = 0.02, respectively) compared with Control group. Furthermore, a significant decrease in Streptococcus from drainage cultures was observed in the Pandemic group (P < 0.05). During the COVID-19 pandemic, a decrease in nosocomial infections was observed in the presence of an increase in alcohol-based hand sanitizer use.